Impact of Good Corporate Governance on Financial Performance of State-Owned Businesses with Risk Management as A Moderating Variable - Erliani, Eni; Widyastuti, Umi; Ulupui, IGKA (International Journal of Social Science, Education, Communication and Economics, 2024)
The objective of this study is to ascertain the impact of the six elements of good corporate governance on the financial performance of state-owned enterprises (SOEs), with risk management acting as a moderating variable. This study employs annual reports on state-owned enterprises (SOEs) listed in Appendix II of the Minister of State-Owned Enterprises Regulation Number PER/MBU/03/2021. The sampling technique employed was purposive sampling, with a research sample comprising 57 SOEs selected from all SOEs for the 2018-2022 period. The data were analyzed using panel data regression analysis with the STATA 17. The results indicated that the Shareholder Aspect had a positive and significant effect on the financial performance of SOEs. In contrast, the aspects of Commitment to Sustainable GCG Implementation, Board of Commissioners, Board of Directors, Disclosure and Transparency of Information, and other factors had no significant effect on the financial performance of SOEs. The findings indicate that risk management exerts a positive and significant influence on the relationship between the Board of Directors aspect and the financial performance of SOEs. Conversely, risk management exerts a negative and insignificant influence on the relationship between the Commitment to Sustainable GCG Implementation aspect, the Board of Commissioners, disclosure and transparency of information, and other factors and the financial performance of SOEs.